Do Pediatric Nephrologists Know Their Educational Competencies? - Seçil Arslansoyu Çamlar; Hatice Şahin (Güncel Pediatri)
Introduction: The competencies in the Medical Specialty Curriculum and Standards Development System (MSCSD) guides trainers in the preparation and execution of the training program and gives learners an idea about the state of mastery that they will reach by graduation. The aim of this study was to evaluate the knowledge of pediatric nephrologists about competencies in the field of specialization. Materials and Methods: In the cross-sectional study conducted between January 2023 and 2024, the knowledge of pediatric nephrologists about specialty competencies was investigated with the two-round Delphi technique. Digital Delphi forms were sent to all pediatric nephrologists in Türkiye via email of the specialty society. In the Delphi form, all competency titles in the MSCSD v.2.3 curriculum were transformed into propositions that could be scored with a 5-point Likert scale. The frequency of 4-5, the difference between quartiles and the median were calculated for each of the statements. For participant consensus on the propositions, the median should be 4, the frequency of 4-5 should be above 70%, and the difference between quartiles should be 2.5 or less. Results: Of the pediatric nephrologists in Türkiye, 59 responded to the first and 136 to the second round Delphi survey. In the first round, full consensus was found in the competency areas other than service delivery, while consensus was found in two of the 72 clinical competencies under the service delivery heading, namely systemic diseases and malignant diseases, and in two of the 26 interventional competencies (diversion and imaging). The analysis of the second round Delphi questionnaire based on this result showed full consensus on all competency headings. The variables of title, gender and training clinic made a difference in consensus. Conclusion: It was found that the level of knowledge of pediatric nephrologists about specialty competencies differed in terms of some variables and knowledge was more limited in young learners for whom competencies are legally binding. In conclusion, it is recommended that learners should be informed about the competencies at the beginning of specialty training and participate in updating the competency list.